A study of side shape analysis of free-form concrete panel using silicone mold and paraffin - Youn, Jongyoung; Bu, Junwon; Cho, Seeun; Jo, Minje; Jeong, Kyeongtae; Lee, Donghoon (Edelweiss Applied Science and Technology, 2024)
This study analyzes the limitations of silicone molds used for free-form panel production and aims to address these issues by utilizing paraffin wax. Silicone molds are known for their reusability and ease of forming free-form shapes. However, the lack of a fixing method between the side and bottom molds makes them vulnerable to lateral pressure. Through FCP production experiments, 3D scans were conducted and shape errors were analyzed. The results showed that while the overall errors were uniform, errors exceeding 3 mm were observed at both ends of the curved sections. These errors are attributed to the installation of CNC equipment and the assembly process of the molds. Therefore, future research should focus on refining the corners and joints of the molds as well as validating complex curved shapes. This study is expected to serve as foundational data for research related to free-form molds.